Optimizing electrical production from renewable energy with electrochemical hybrid-energy storage system at EGAT, Mae-Moh Site - Artit Teeprueksa; Atipoang Nuntaphan; Yuttana Mona; Xiong Shu; Feng Gong; Tanakorn Wongwuttanasatian; Amnart Suksri; Konlayutt Punyawudho (Energy Nexus, 2025)
The optimization of the renewable energy system was examined through mathematical simulations utilizing the HOMER program. The simulations were performed in alignment with the real implementations called “demonstration site”, where was effectively developed with power output of 10 kW at the Mae Moh power plant by EGAT. The energy generation from both optimized model and practical setup successfully fulfilled the energy demand throughout the year. Cost-benefit analysis showed that the optimized model had 57% lower LCOE and NPC than a demonstration site. Furthermore, the optimization was conducted to achieve higher power output within the range of 350–460 kW under dynamic load conditions, as well as within the 5 MW range for power plant. The average energy generated by the simulation over a year was sufficient for both scenarios (i.e., 254% for 460 kW and 303% for 5 MW), even under the lowest solar irradiation conditions observed from June to August. The hybrid energy storage system, which uses batteries and hydrogen, was the most cost-effective in both situations, according to LCOE and NPC. Under consistent modeling parameters (i.e., no power outages throughout a year), the LCOE for 5 MW ($0.127/kWh) is 25.73% lower than for 460 kW ($0.171/kWh). Consequently, increased power production rates lead to reduced investment and operating costs compared to lower power generation rates.